Stakeholder Preference towards Conservation of Marine Mega Fauna: Olive Ridley Turtle (Lepidochelys olivacea) (Eschscholtz, 1829) Conservation Dilemma in Odisha - Ashok, Arathy; Raghu Prakash, R. (Fishery Technology, 2019)
Conservation of marine megafauna is a complex issue as it is linked to ecological, socio-economic and political dimensions. Olive ridley turtle (Lepidochelys olivacea) (Eschscholtz, 1829) conservation along Odisha coast is one of such dilemma which often leads to conflict between different stakeholders. Considering the mass nesting status, incidental mortality and fisheries linkages, several legislations to conserve the turtles were evolved from time to time imposing regulation on fishing activities in Odisha coast. The study reviews the scenario for conservation of the turtles along Odisha coast and fishers’ awareness, perception and preferences towards alternate management measures. Study found that 81.58% of the fishermen preferred an alternative conservation scenario either with a reduction in closure time, area closure or both. Even though, they were aware about the need of conservation of marine turtles, it was found to be partial. Adequate research on the ecology, distribution/redistribution and bycatch of olive ridley turtles in Odisha and proper awareness generation with the updated information among the fishers was found to be necessary for ensuring better conservation management. Study on spatial distribution of turtles and its association with the existing fishing grounds in a participatory bottomup approach can help in making targeted conservation measures more effective. Ecological dimension of conservation may be coupled with socioeconomic dimensions for a sustainable ecosystem management